An improved algorithm using a Health Canada‐approved DNA‐image cytometry system for non‐invasive screening of high‐grade oral lesions. (3rd February 2021) - Parfenova, Ekaterina; Liu, Kelly Y. P.; Harrison, Alan; MacAulay, Calum; Guillaud, Martial; Poh, Catherine F.
Abstract: Background: DNA‐image cytometry (DNA‐ICM) is able to detect gross alterations of cellular DNA‐content representing aneuploidy, a biomarker of malignancy. A Health Canada‐approved DNA‐ICM system, ClearCyte ® in combination with a cytopathologist's review, has demonstrated high sensitivity (89%) and specificity (97%) in identifying high‐grade oral lesions. The study objective was to create an improved automated algorithm (iClearcyte) and test its robustness in differentiating high grade from benign reactive oral lesions without a cytopathologist's input. Methods: A set of 214 oral brushing samples of oral cancer (n = 92), severe dysplasia (n = 20), reactive lesions (n = 52), and normal samples (n = 50) were spun down onto slides and stained using Feulgen‐Thionin reaction. Following ClearCyte ® scan, nuclear features were calculated, and nuclei categorized into "diploid, " "hyperdiploid, " "tetraploid, " and "aneuploid" DNA ploidy groups by the ClearCyte ® software. The samples were randomized into training and test sets (70:30) based on patient's age, sex, tobacco use, and lesion site risk. The training set was used to create a new algorithm which was then validated using the remaining samples in the test set, where sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: The proposed iClearCyte algorithm (>1 "aneuploid" cell or ≥ 1.7% combined "hyperdiploid" and "tetraploid" nuclei frequency) identified high‐grade samples with sensitivity, specificity, PPV, and NPV of 100.0%, 86.7%, 89.7%, and 100.0%, respectively, in the test set. Conclusion: The iClearCyte test has potential to serve as a robust non‐invasive automated oral cancer screening tool promoting early oral cancer detection and decreasing the number of unnecessary invasive biopsies.